(untitled) (Tri-Chandra Journal of Anthropology, 2024)
This paper explores the effects of climate change on the distribution of Yartsagunbu based on local people’s experiences. Yartsagunbu (Ophiocordyceps Sinensis) is a high-valued fungus that is understood as a stamina enhancer and endoparasitic complex of the parasitic fungus. It is found in the alpine and subalpine grasslands of the Himalayas and the Tibetan Plateau, at 3,000–5,200 meters above sea level. Yartsagunbu has been a significant livelihood resource and generates significant income for the collectors in rural Dolpa, Mugu, Jumla, Bajhang, and Manang of Nepal. This paper has explored climate change and its effects on the Yartsagunbu collectionin the Dolpa district. This brings out the Tarali people’s local experiences and perceptions of climate change and its effect on Yartsagunbu. Data and information for the study were collected from multiple fieldworks during the period 2019, 2020, and 2021. Furthermore, it is supported by personal experience of Yartsagunbu harvesting from the years 2001 to 2005. Present and past trends of Yartsagunbu harvesting experience and perception are collected by interviews with Yartsagunbu collectors, traders, and senior citizens. The finding of the study reveals that climate change is affecting the Yartsaguubu abundance and livelihood of Yartsagunbu collectors.